Rehabilitation through parole system in Malaysia: the role of optimism as mediating variable in the relationship between self-efficacy and resilience - Wan Shahrazad Wan Sulaiman; Fauziah Ibrahim; Mohamad Suhaimi Mohd; Salina Nen; Norulhuda Sarnon; Khadijah Alavi (Penerbit Universiti Kebangsaan Malaysia, 2016)
Identifying the personal characteristics of parolees that can reduce the likelihood of committing crimes is a great challenge to prison officers in order to ensure that rehabilitation process is handled success-fully. The changes recommended to prisoners under parole are to increase their self-efficacy, develop-ing optimism and maintaining a high level of resilience. This study employs a cross-sectional survey research design. A total of 280 prisoners undergoing parole monitoring were recruited as respondents. A set of questionnaire was used consisting of the General Self-Efficacy Scale, the Positive Thinking Rating Scale and a self-developed resilience scale. Results showed that there were significant correla-tions between self-efficacy, optimism and resilience. Further, findings indicated that optimism partially mediated the relationship between self-efficacy and resilience. Implications are discussed in the context of preventing recidivism among parolees and strategies to increase effectiveness of rehabilitation in the parole system.